Benefits of stronger Neo‐Minophagen C in acute hepatitis after transarterial chemoembolization therapy for hepatomas. Issue 1 (28th February 2022) - Huang, Wen‐Chieh; Lin, Yu‐Min; Kuo, Hsing‐Tao; Sheu, Ming‐Jen; Feng, Yin‐Hsun; Feng, I‐Che; Sun, Chi‐Shu; Hsieh, Ping‐Hsin; Lim, Poh‐Poo; Chen, Chi‐Hsing
Abstract: Hepatitis after transarterial chemoembolization (TACE) is common. Stronger Neo‐Minophagen C (SNMC) has demonstrated benefits in patients with hepatitis. We aimed to determine its usefulness in post‐TACE hepatitis in patients with hepatomas. Overall, 60 patients with hepatomas who were treated with TACE were prospectively analyzed; of these, 30 patients underwent SNMC treatment after TACE. Daily serial changes in the liver function tests (serum levels of aspartate aminotransferase [AST], alanine aminotransferase [ALT], total bilirubin, prolonged prothrombin time, and international normalized ratio [PT/INR]) were compared between the two groups. Common complications, such as fever, nausea, and emesis, were also compared. There were no significant differences in baseline characteristics between the groups ( P > .05). Although the absolute value of AST/ALT was lower in the SNMC treatment group, differences between the groups were nonsignificant. Total bilirubin and PT/INR levels were significantly different between the groups ( P = .03 and .02, respectively), thus indicating potential SNMC effects on hepatocyte regeneration. Significant differences were also observed between the groups with respect to fever and nausea/emesis (both P = .002). Side effects of SNMC, such as hyperkalemia or hypertension, were not significantly different between the groups. SNMC demonstrated some benefits in patients with hepatomas after TACE.